If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -1) = 2x + 14 Reorder the terms: 4(-1 + 2x) = 2x + 14 (-1 * 4 + 2x * 4) = 2x + 14 (-4 + 8x) = 2x + 14 Reorder the terms: -4 + 8x = 14 + 2x Solving -4 + 8x = 14 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 8x + -2x = 14 + 2x + -2x Combine like terms: 8x + -2x = 6x -4 + 6x = 14 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 6x = 14 + 0 -4 + 6x = 14 Add '4' to each side of the equation. -4 + 4 + 6x = 14 + 4 Combine like terms: -4 + 4 = 0 0 + 6x = 14 + 4 6x = 14 + 4 Combine like terms: 14 + 4 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| 10x+22=13x+10 | | 14x+14=36 | | 2x+5=8X+25 | | 4y+20-y-4=6 | | 5r^2+33r+40= | | 8(x-2)=40 | | 7-3x+9=5x | | -0.02x^2+1.4x-12=0 | | 6(b+5)+2=22+b | | x+10=43 | | -80000x+2000000=4200000 | | 13+8x=11-4 | | 5xn=400 | | -5(3+11n)=-10(10-3n) | | 11/2+12/6= | | -4x+10x=0 | | -80000x+2000000=3600000 | | 5(k-3)+6=-2k+12 | | ln(5)+ln(x-1)=0 | | 2/6+5/2= | | 7n-10=5n+2 | | -3x-11y=3 | | 5(2f+6)=5f-9 | | -4(1+p)=-8-2p | | 6x-12y=-6 | | 0=2x^2-25x+57 | | 8=18-5x | | 20x^2+12x-56=0 | | f(x)=3x^2+24x | | 4=17-13x | | 0=2x^2-19x+30 | | 45=3x^2 |